PERLINDUNGAN HUKUM TERHADAP KEPENTINGAN PARA PIHAK DI DALAM MERGER BANK - Dani Amran Hakim (Universitas Lampung, 2015)
The legal protection of interests of the parties in the merger of banks, which is formulated into the problem as follows a) Is the legal basis for bank mergers? b) How is the legal protection of the parties in a bank merger? Merger is one of the company's development and growth. Merger is also one other alternative for capital investment through internal and organic growth. In banking mergers regulated in Law Number 10 of 1998. In the implementation of the merger must also consider the interests of the parties, namely, 1) the interests of the shareholders, 2) the interests of the depositors, 3) the interest of the bank employees, and 4) the interests of officials. Keywords: Protection Law, the Parties, Bank Merger